Robert of Torigni’s “pragmatic literacy”: some theoretical considerations - Benjamin Pohl (Tabularia)
This article offers some theoretical considerations on the literacy of Robert of Torigni (1106-1186), monk/prior of Le Bec (dép. Eure, cant. Brionne) and abbot of Mont-Saint-Michel (dép. Manche, cant. Pontorson), and one of the most celebrated historians of the twelfth century. In recent years, scholars have shown a renewed interest in Robert as an author and scribe, including his handwriting, his librarianship, his use of archival sources, and his working methods as a historian. At the same time, however, there is no study that approaches Robert’s relationship with the written word from a conceptual point of view. The present article attempts to fill this lacuna by revisiting Robert’s literary activities in the light of what is known amongst medievalists as the concept of “pragmatic literacy”.